Harvard Business Review on Managing External Risk - Authors (Harvard Business Press, 2009)
Businesses today are operating amid unprecedented uncertainty. The greater the uncertainty, the more ominous and numerous the threats to your company. To manage external risk, you'll need to select the right analytical tools and incorporate risk into your strategic decision making. This collection shows you how, providing powerful frameworks, tools, and examples for mastering this crucial competency. The Harvard Business Review Paperback series is designed to bring today's managers and professionals the fundamental information they need to stay competitive in a fast-moving world. From the preeminent thinkers whose work has defined an entire field to the rising stars who will redefine the way we think about business, here are the leading minds and landmark ideas that have established Harvard Business Review as required reading for ambitious businesspeople in organizations around the globe.